Impacto de un plan de marketing digital en las ventas de una empresa de telecomunicaciones y seguridad electrónica. - Vilcarromero-Bazán, A.I. (2024)
A telecommunications and electronic security company from Cajamarca is growing, but its sales volume suffers from drastic fluctuations and its digital sales channels have not been given the necessary relevance. Therefore, this research aims to analyze the influence of a digital marketing plan in the sales of this company. For this purpose, an applied, quantitative and preexperimental study was carried out, in which 52 transactions representing the company's sales for the months of March, April and May were considered as a sample. Two summary sheets and a questionnaire were used to collect the data. The results obtained are as follows: it was possible to develop a digital marketing plan according to the SOSTAC methodology; in terms of web positioning, 122 visits to the website were obtained and a conversion rate of 4.82%; through social networks, the number of messages received increased by 50%; in terms of email marketing strategy, an opening rate of 29.48% and a bounce rate of 7.15% were obtained; finally, in terms of sales level, an increase of 2.71% was obtained. It can be concluded that a digital marketing plan has a positive impact on a company's sales.